Diagnostic yield of various traditional laboratory investigations in the diagnosis of cutaneous leishmaniasis - Mashhood, Asher Ahmed (Journal of Pakistan Association of Dermatologists, 2017)
Background Leishmaniasis is a tropical protozoal infection endemic in certain areas ofPakistan. The clinical diagnosis of disease can be confirmed by various laboratory investigations like direct microscopy, culture, Leishmanin test and newer serological tests. Objective To determine the diagnostic yield of Leishmanin test, direct microscopy and leishmania culture in the diagnosis of cutaneous leishmaniasis inPakistan. Patients and methods In this observational study conducted at the Skin Department, PNS Shifa and DESTO Laboratories,Karachi, 40 patients were included. Leishmanin test, direct microscopy and leishmania culture was performed on all these patients. Results Leishmanin skin test was positive in all the 40 patients (100%), direct microscopy of the smear in 28 patients (70%) and Leishmania culture in 32 patients (80%). Conclusion Traditional methods of diagnosis have a high yield of positivity in the diagnosis of cutaneous leishmaniasis. Â 